Description of Hypotension in Cesarean Section Patients Under Spinal Anesthesia Using Conventional and Enhanced Recovery after Surgery Methods - Eko Yulianto; Dwi Novitasari; Asmat Burhan (Indonesian Journal of Global Health Research, 2025)
Enhanced Recovery After Surgery (ERAS) is a multimodal perioperative management aimed at faster recovery from major surgery, reducing the risk of complications, and shortening the length of stay compared to conventional perioperative methods. Hypotension is a side effect of a cesarean section with spinal anesthesia. This study aims to describe hypotension in patients undergoing cesarean sections with conventional spinal anesthesia methods and the Enhanced Recovery After Surgery (ERAS) method. This study used a quantitative research method with a descriptive design and a cross-sectional approach. The sampling technique was purposive sampling with a total of 40 cesarean section patients, consisting of 20 respondents in the conventional spinal anesthesia group and 20 respondents in the ERAS spinal anesthesia group. Blood pressure measurements were taken before and after spinal anesthesia using a bedside monitor. The data obtained included age and blood pressure, which were analyzed using statistics. The results showed that in the conventional spinal anesthesia group, 15 respondents experienced hypotension (75%), and 5 respondents did not experience hypotension (25%). In the Enhanced Recovery After Surgery (ERAS) spinal anesthesia group, 7 respondents experienced hypotension (35%), and 13 respondents did not experience hypotension (65%).